2018
DOI: 10.1186/s40644-018-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

An international survey on hybrid imaging: do technology advances preempt our training and education efforts?

Abstract: BackgroundHybrid PET/CT and PET/MRI are increasingly important technologies in the evaluation of malignancy and require cooperation between radiologists and specialists in molecular imaging. The aim of our study was to probe the mindsets of radiological and nuclear medicine professionals in regard to current hybrid imaging practice and to assess relevant training aspirations and perceived shortfalls, particularly amongst young professionals. In this context, we initiated an international survey on “Hybrid Imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…Our survey had similar findings regarding hybrid imaging. However, hybrid imaging faces many practical and political challenges, since it is driven largely by both nuclear medicine specialists and radiology specialists, whose daily practices and specialty curricula usually do not align well (14). Until these issues are resolved, other professional recommendations by renowned experts may-at least at the local level-be useful on training and reporting practices (26,30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey had similar findings regarding hybrid imaging. However, hybrid imaging faces many practical and political challenges, since it is driven largely by both nuclear medicine specialists and radiology specialists, whose daily practices and specialty curricula usually do not align well (14). Until these issues are resolved, other professional recommendations by renowned experts may-at least at the local level-be useful on training and reporting practices (26,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid imaging modalities, such as PET/CT, stand out from the range of typical radiologic or nuclear medicine imaging examinations. Despite their potential to use synergistic and complementary diagnostic information, existing ownership and training schemes affect the performance of such investigations (14). In light of a growing base of hybrid imaging systems and the potential to increase diagnostic accuracy from combined, ''anatometabolic'' imaging (15), we intended to probe the current status of PET/CT reporting with regard to oncology patient management.…”
mentioning
confidence: 99%
“…The challenges of competencies and training in PET/MRI were also investigated amongst radiologists and nuclear medicine physicians. In a study from 2018, Beyer et al (2018) analysed data from an international survey and found that the PET/MRI field was still developing and there were as yet no perfect combinations for training. The authors found that there was a drive for physicians to collaborate and learn from each other and maintain an up-to-date training record.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first commercially available wholebody PET-MRI systems were installed in 2010 by Philips as two separated systems: a PET and MRI with the patient table moving between the two (Fendler et al, 2016). A year later, Siemens gained approval for the first simultaneous whole-body PET/MRI system (Beyer et al, 2018). By August 2017, there were about 130 systems installed worldwide including the newly Food and Drugs Authority (FDA)-approved general electric (GE) TOF (time of flight) PET/MRI (Beyer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation